2021
DOI: 10.1021/acs.molpharmaceut.1c00366
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Fate of Nanoparticles Designed for the Nasal Delivery of Poorly Soluble Drugs

Abstract: Nanoparticles are promising mediators to enable nasal systemic and brain delivery of active compounds. However, the possibility of reaching therapeutically relevant levels of exogenous molecules in the body is strongly reliant on the ability of the nanoparticles to overcome biological barriers. In this work, three paradigmatic nanoformulations vehiculating the poorly soluble model drug simvastatin were addressed: (i) hybrid lecithin/chitosan nanoparticles (LCNs), (ii) polymeric poly-ε-caprolactone nanocapsules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 98 publications
0
38
0
Order By: Relevance
“…Nanoparticles 20 nm in size had twice the penetration rate of 100 nm nanoparticles, which themselves were twice as effective in penetration than 500–1,000 nm particles (3.25%:2%:1.25% of particles, respectively, reach systemic circulation). Coating the PS nanoparticles with poloxamine 908 (a PEG-like polymer) reduced cellular interactions and thus decreased penetration, while coating with mucoadhesive chitosan doubled particle delivery into systemic circulation (0.3–0.6%) [ 122 ]; similar results were shown comparing polysorbate 80 and chitosan-coated lecithin nanoparticles [ 119 ].…”
Section: Nano-delivery Design Considerationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Nanoparticles 20 nm in size had twice the penetration rate of 100 nm nanoparticles, which themselves were twice as effective in penetration than 500–1,000 nm particles (3.25%:2%:1.25% of particles, respectively, reach systemic circulation). Coating the PS nanoparticles with poloxamine 908 (a PEG-like polymer) reduced cellular interactions and thus decreased penetration, while coating with mucoadhesive chitosan doubled particle delivery into systemic circulation (0.3–0.6%) [ 122 ]; similar results were shown comparing polysorbate 80 and chitosan-coated lecithin nanoparticles [ 119 ].…”
Section: Nano-delivery Design Considerationsmentioning
confidence: 96%
“…For nanoparticles of similar size, the surface chemistry of the nanoparticle primarily dictates its primary transport pathway; introducing hydrophobic surface chemistry (e.g. using lipid nanoparticles) can help increase transcellular transport while the introduction of hydrophilic groups and penetration enhancers can improve paracellular travel [ 119 ]. Cationic surface charge in particular can govern two key biological responses to nanoparticles: (1) disrupt tight junctions to allow for increased binding to, and subsequent penetration through, the nasal epithelium; and (2) complex with the highly anionic nasal mucus to promote transmucosal transport [ 16 ].…”
Section: Nano-delivery Design Considerationsmentioning
confidence: 99%
“…This process could be further assessed by the ex vivo fluorescent bio-imaging and confocal microscopic techniques. On the basis of this extensive in vivo and ex vivo research, these implications of nanoparticle toxicities were found to be size-dependent ( Anton et al, 2008 ; Clementino et al, 2021 ).…”
Section: Nanotoxicology and The Female Reproductive Systemmentioning
confidence: 99%
“…Several features may hamper drug absorption through the nasal mucosa, such as molecular weight and permeability. The amount of drug transported from nose to the systemic circulation can be quite variable, ranging from almost 100% to less than 1% of the administered dose [34].…”
Section: Mucoadhesive Evaluation Of Optimized Free and Drug-loaded Eu...mentioning
confidence: 99%